Use of TUBB3 for patient stratification and prognosis in lung cancer. (April 2015) - Jakobsen, Jan Nyrop; Santoni-Rugiu, Eric; Sørensen, Jens Benn
SUMMARY : Microtubules play a crucial role in the eukaryote replicative cell machinery and antimicrotubule drugs such as vinca alkaloids and taxanes are important drugs in the treatment of several solid tumors. TUBB3 has in retrospective studies shown to be of significance with regard to outcome in NSCLC patients treated with anti-microtubule drugs. However, it is still controversial whether or not TUBB3 has a prognostic or a predictive value. This review provides an overview of preclinical and clinical studies that have presented data on the role of TUBB3 in NSCLC.